Reduce Child Obesity: A Guide to Using the Kid's Choice Program in School and at Home - Hendy, Helen; Williams, Keith; Camise, Thomas (Rowman & Littlefield Publishers, 2013)
Reduce Child Obesity: A Guide to Using the Kid’s Choice Program in School and at Home provides school leaders with a practical guide for applying the Kid's Choice Program (KCP), which is a school-based program to promote healthy behaviors and reduce the risk of child obesity. The KCP Guide may also be used by health researchers to document the program’s effectiveness. The KCP was researched with 1000+ school-age children and documented to be easy-to-use, low in cost (at $2 per child per month), and effective for increasing weight management behaviors in children (eating fruits and vegetables, choosing low-fat and low-sugar drinks, exercising daily). Research also documents that the KCP improves weight status in overweight children (for intervention) and normal-weight children (for prevention). Additionally, the program improves diets of children who are picky eaters. The KCP can be delivered by small teams of 2-4 volunteers (such as parents) after five minutes of training. It uses simple procedures (children wear nametags, "stars" punched in nametags when children choose healthy behaviors, weekly Reward Days let children trade "stars" for small prizes). The KCP is well-accepted by children, parents, and school staff. For more information on the KCP, please visit kidschoiceprogram.org.